2018
DOI: 10.1016/j.jelectrocard.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of number of co-existing rotors and inter-electrode distance on accuracy of rotor localization

Abstract: Background Conflicting evidence exists on the efficacy of focal impulse and rotor modulation on atrial fibrillation ablation. A potential explanation is inaccurate rotor localization from multiple rotors coexistence and a relatively large (9–11 mm) inter-electrode distance (IED) of the multi-electrode basket catheter. Methods and results We studied a numerical model of cardiac action potential to reproduce one through seven rotors in a two-dimensional lattice. We estimated rotor location using phase singular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Whatever, electrophysiology mapping system is used to mapping AF, there is a debate in the literature with regards to the required time duration of VEGMs to be used detecting/tracking rotors. Several studies have used ≤ 10 s [13][14][15], while others used segments ≥ 30 s [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Thus, our results are expressed in two groups; group A ≤ 30 s and group B > 30 s. In order to investigate the time duration needed to produce a representative rotor density map, two time segments in each group were selected (group A 10 -30 s, group B 45-60 s) to distinguish the difference of the spatiotemporal changes of rotors in each rotor density map in comparison with the rotor density maps of 300 s segment recording (gold standard).…”
Section: Discussionmentioning
confidence: 99%
“…Whatever, electrophysiology mapping system is used to mapping AF, there is a debate in the literature with regards to the required time duration of VEGMs to be used detecting/tracking rotors. Several studies have used ≤ 10 s [13][14][15], while others used segments ≥ 30 s [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Thus, our results are expressed in two groups; group A ≤ 30 s and group B > 30 s. In order to investigate the time duration needed to produce a representative rotor density map, two time segments in each group were selected (group A 10 -30 s, group B 45-60 s) to distinguish the difference of the spatiotemporal changes of rotors in each rotor density map in comparison with the rotor density maps of 300 s segment recording (gold standard).…”
Section: Discussionmentioning
confidence: 99%
“…The rotors were defined as the phase singularities of the phase map as described previously [12]. To make our work clinically applicable, the transmembrane potential derived from the model was converted to unipolar and subsequently to bipolar signals ( Figure 1B) [18].…”
Section: Model Of Spiral Wavesmentioning
confidence: 99%
“…We recently investigated how spatial resolution affects interpretation of AF recordings, expressing spatial resolution requirements as a linear function of the spatial wavelength, and found that high-density multipolar catheters provide sufficient resolution, but basket catheters are prone to false rotor detections [ 50 ]. Aronis et al considered the effects of multiple co-existing rotors on resolution requirements in an in silico study and found that including more than one rotor increased errors 10-fold, suggesting higher resolution requirements for cases with multiple sources [ 51 ]. Jacquemet used a statistical model to investigate the effects of interelectrode spacing and rotor number and showed an increase in false positive and false negative phase singularity detections with increasing interelectrode distance [ 52 ].…”
Section: Approaches To Mapping Sources Of Myocardial Fibrillationmentioning
confidence: 99%